2011
DOI: 10.1002/cncr.26190
|View full text |Cite
|
Sign up to set email alerts
|

AAML03P1, a pilot study of the safety of gemtuzumab ozogamicin in combination with chemotherapy for newly diagnosed childhood acute myeloid leukemia

Abstract: BACKGROUND:The development of antigen-targeted therapies may provide additional options to improve outcomes in children with acute myeloid leukemia (AML). The Children's Oncology Group AAML03P1 trial sought to determine the safety of adding 2 doses of gemtuzumab ozogamicin, a humanized anti-CD33 antibody-targeted agent, to intensive chemotherapy during remission induction and postremission intensification for children with de novo AML. METHODS: AAML03P1 enrolled 350 children with previously untreated AML. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
178
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 178 publications
(192 citation statements)
references
References 46 publications
11
178
0
3
Order By: Relevance
“…180,[183][184][185] Recent data from a prospective nonrandomized COG trial showed that GO did not cause increased toxicity, but data on efficacy are pending. 186 However, as the approved indications for GO have been revised in the United States by the FDA request, it may not be easily available for use in pediatric AML outside of clinical trials. …”
Section: Antibody-targeted Drugsmentioning
confidence: 99%
“…180,[183][184][185] Recent data from a prospective nonrandomized COG trial showed that GO did not cause increased toxicity, but data on efficacy are pending. 186 However, as the approved indications for GO have been revised in the United States by the FDA request, it may not be easily available for use in pediatric AML outside of clinical trials. …”
Section: Antibody-targeted Drugsmentioning
confidence: 99%
“…Details of these studies have been previously described. [23][24][25][26] AAML03P1 (N 5 350) and CCG-2941/2961 (N 5 1106) enrolled patients 0 to 21 years of age, whereas AAML0531 (N 5 1070) enrolled patients that were 0 to 30 years of age. S0106 (N 5 595) enrolled patients 18 to 60 years of age.…”
Section: Patient Samplesmentioning
confidence: 99%
“…Twenty-seven articles were included based on their abstracts. After reading full-text articles, 14 studies were included in this study [4,[21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Search Strategymentioning
confidence: 99%